The accompaniment model in insertion companies as a strategy to improve the employability of people in a situation and / or risk of social exclusión - Salinas Tomás, Manuel Francisco (REVESCO. Revista de Estudios Cooperativos, 2023)
In recent decades, social economy has experienced an important expansion as an economic model that offers new responses to the system’s socioeconomic problems, placing people and their needs ahead of capital and profits. Within social economy organization, we can point insertion companies as social companies that in the current situation of socioeconomic crisis and generalized job insecurity, within the framework of active employment policies, stand out as instruments that fight against exclusion of people with difficulties in social and labor integration promoting their employability and quality of life. Together with the support of public institutions, the social, labor and educational accompaniment that is carried out in them, happens to be the key factor in terms of the success of the social and labor inclusion of the people in a situation of exclusion on whom they work.
Keywords: Employability; Social exclusion; Social and labor inclusion; Career path; Social and labor support